Reaction pathway analysis for differences in motion between C-core and Si-core partial dislocation in 3C-SiC - Jing YANG (The Japan Society of Mechanical Engineers, 2015)
Reaction pathway analysis was carried out to investigate the activation energy barriers of Shockley partial dislocation mobility in 3C-SiC. For each partial dislocation, there are two types of dislocations according to which kind of atom, Si or C, comprises the core edge of the dislocation line. In this paper, the partial dislocation is simulated by Vashishta potential functions. Moreover, the activation energy of kink pair nucleation and kink migration are investigated by reaction pathway analysis. The dependence of the activation energy on the driving shear stress is also discussed. The results show that during kink migration, 30° partial dislocations have a lower activation energy barrier than 90° partial dislocation. And, C-core partial dislocations have a higher activation energy barrier than Si-core dislocations for both degrees of partial dislocations during kink migration and nucleation. This conclusion is consistent with the experimental result that Si-core dislocations migrate more readily than C-core dislocations. Furthermore, we found that partial dislocations with larger distance between the dangling bond atoms along the dislocation line have higher activation energy barriers. Based our calculation results, we propose new models to account for the morphological differences in the dislocation lines.